(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article presents the results of a study of current problems of forming a culture of information security and media immunity of young people through educational processes in the context of digital transformations. In particular, the role and tasks of academic disciplines of the social and humanitarian educational direction in improving the culture of information security, forming and strengthening media immunity among young people were studied. Emphasizing that the problems associated with this topic are systemic, specific ways to solve them are proposed.